If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -9) = 2 + -6x Reorder the terms: 3(-9 + x) = 2 + -6x (-9 * 3 + x * 3) = 2 + -6x (-27 + 3x) = 2 + -6x Solving -27 + 3x = 2 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -27 + 3x + 6x = 2 + -6x + 6x Combine like terms: 3x + 6x = 9x -27 + 9x = 2 + -6x + 6x Combine like terms: -6x + 6x = 0 -27 + 9x = 2 + 0 -27 + 9x = 2 Add '27' to each side of the equation. -27 + 27 + 9x = 2 + 27 Combine like terms: -27 + 27 = 0 0 + 9x = 2 + 27 9x = 2 + 27 Combine like terms: 2 + 27 = 29 9x = 29 Divide each side by '9'. x = 3.222222222 Simplifying x = 3.222222222
| m/18=39 | | 545346685769807-7856867+6578639758= | | Q=mL | | 9-x/3^2=-33 | | 5(x•2)=100/2 | | (8x+15)=3x | | 9-x^2/3=-33 | | 25+5x^2+30x=0 | | e^14= | | 25+5x^2+30=0 | | -2/3x-1/3=x/3-4/3 | | f(x+1)=4x^2+7x-5 | | 12.5=1.5x | | 13=2n^2-3n | | 4(x+9)=15 | | 3x-2=3x-7 | | 7x+1=5x-4 | | 5/63-9(-2)/7 | | 4b+7=5b-3 | | (3p-4)x(3p-4)=0 | | 8x+10=-25x+20 | | 15(x-25)=180 | | 4-5/2 | | 5x+2-2x=4x-4 | | 2y-7x=-17 | | 12+q=30 | | -100=12+-5 | | .60x=320 | | 7a^3=8 | | 3M+8m-2m=-126 | | (5)/(6)=-(3)/(8)b | | 18x+10-2x=4(x-5) |